The Prevalence of Playing-related Musculoskeletal Disorders (PRMSD) Among Professional Orchestra players - Maria Gomes de Sousa, Henry Johannes Greten, Jorge Machado e Daniela Coimbra, Cláudia (Música Hodie, 2015)
The prevalence of playing-related musculoskeletal disorders (PRMSD) among musicians is high and several causes, such as the quality of working conditions can influence their onset. The aim of this study was to study the influence of working conditions on the prevalence of PRMSD. Three professional orchestras were invited to take part in the study. They were then divided into two groups according to the working conditions they offered. Group A was considered to present adequate working conditions and group B was not. PRMSD and its intensity, as measured by Verbal Numeric Scale (VNS), were registered through an individual semi-structured interview. Group B presented a higher percentage of self-reported PRMS complaints (67.4%) than group A (59.4%). VNS values were also higher (p value= 0.021) in group B (VNS=5.1) than in group A (VNS=4.0). Results suggest that the prevalence and the severity of PRMSD could be reduced by adequate working conditions.Palavras-chaves: Working conditions; Playing-related musculoskeletal disorders; Orchestra musicians; Working related problems; Professional musicians.